Turkeys, Pilgrims, and Indian corn : the story of the Thanksgiving symbols - Barth, Edna.; Arndt, Ursula (New York : Seabury Press, 1975)
Traces the history of this American harvest celebration and the development of its symbols and legends.
"A Clarion book."
Includes bibliographical references and index.
Keywords: Thanksgiving Day -- Juvenile literature; Thanksgiving Day; Holidays